Roadless Rules: The Struggle for the Last Wild Forests - Harvard Business School Publishing Corporation (Island Press, 2009)
Roadless Rules is a fast-paced and insightful look at one of the most important, wide-ranging, and controversial efforts to protect public forests ever undertaken in the United States.